Analisis Faktor yang Mempengaruhi Keputusan Berbelanja Online - Chandra, Dharnita; Rini, Puspa; Sattar; Suri, Dharlinda; Nilowardono, Sengguruh (Jurnal EMT KITA, 2025)
The study aims to determine the influence of promotion and purchase interest on online shopping decisions for Cardinal Product Consumers. The sample in this study was 100 people, all of whom were taken from the residents of Tegal City. Data collection through questionnaires and data analysis using SPSS 25. Data analysis includes tests: Validity, Normality, Classical Assumptions, Multiple Linear Regression Analysis and Hypothesis. The results of the study indicate that promotion and purchase interest have a positive and significant effect on online shopping decisions for Cardinal Product Consumers. Based on the determination coefficient value (R2), it was obtained at 79 %, meaning that the online shopping decision variable for Cardinal Product consumers is influenced by promotion and purchase interest.